Modified Limbal Incision: An Easy and Safe Window for Extraocular Muscle Surgery - Muhammad Khalil, Tayyaba Gul, Mian M. Shafique, Nadeem H. Butt (Pakistan Journal of Ophthalmology, 2008)
Purpose: To find out the advantages and disadvantages of modified limbal incision as an approach to horizontal extraocular muscles during squint surgery and its comparison with ‘over the muscle’ conjunctival incision. Material and Methods: Total of 67 patients of squint were included in this prospective study which was conducted between March 1999 and October 2002. Both male and female patients of all age groups and all types of squints were included. These patients were admitted for surgery after proper assessment including history, examination and investigations. In 36 patients modified limbal incision was given in the conjunctiva (Group-I) while remaining 31 patients underwent ‘over the muscle’ conjunctival incision for approaching the extraocular muscles (Group-II). Results: Approach to the extraocular muscles was easy in 94.5% cases with modified limbal incision as compared to 80.5% (25 out of 31) in over the muscle incision. No help of assistant was required for suturing of the wound during the Modified limbal approach while it was required in 59% (17/31) of cases in Group- II. Although conjunctiva was congested in good number of patients in both groups on first post op day, yet more patients were comfortable in first Group than in second group. Removal of stitches in modified limbal approach was almost non existing while in comparison stitches had to be removed in almost one third of cases in the other group. Conclusion: Modified limbal conjunctival incision is a safe and quick approach to operate on extraocular muscles both in esotropia and exotropia, equally good for recessions and resections. Although majority of patients postoperatively have red eyes yet most of the patients are relatively more comfortable as compared to “over the muscle incision”. Only two stitches are required to close the incision. Mostly there is no need to remove these stitches.